On-demand autophagic network adaptations upon limited lipid availability. Issue 7 (2nd July 2020) - Kern, Andreas; Behl, Christian
ABSTRACT: The de novo synthesis of autophagic vesicles is strongly dependent on sufficient lipid supply. Recently, the RAB GTPase RAB18 was shown to affect autophagy by mediating fatty acid release from lipid droplets, which are lipid sources for autophagosome formation. The stable loss of RAB18 interfered with fatty acid release from the lipid reservoirs and provoked autophagy network adaptations aiming to maintain autophagic activity under lipid limiting conditions.